Pengaruh Kemudahan Penggunaan, Persepsi Manfaat, Pengetahuan, Dan Risiko Terhadap Minat Penggunaan E-Payment Qris Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang - Muhammad Rizqi Aditya; Mohammad Rizal; Alfian Budi Primanto (UNIVERSITAS ISLAM MALANG, 2026)
Abstract The transformation of financial technology has changed the transaction patterns of students towards digital payment systems, one of which is through the Indonesian Standard Quick Response Code (QRIS). This study aims to examine the influence of ease of use, perceived benefits, knowledge, and risk on students' interest in using QRIS at the Faculty of Economics and Business, Islamic University of Malang. The approach used is quantitative with a causal associative research design. Data were collected through an online questionnaire from 108 active students who had used e-payment at least three times, then analyzed using multiple linear regression with the help of IBM SPSS version 25. The results of the analysis show that perceived benefits and knowledge levels have a positive and significant effect on interest in using QRIS. Meanwhile, ease of use and risk did not have a significant partial effect. However, collectively, all independent variables had a significant effect on the interest in using QRIS. The research model explained 50% of the variation in the interest in using QRIS. Keywords: QRIS, Interest In Using, Perceived Benefits, Knowledge, Risk.